The The main aspects of cultural influence between the Turkic Khaganates and the Chinese Empire - Ахмет Ташагыл; Мадина Аманова (Turkic Studies Journal)
The article explores the mutual cultural influence between the First and the Second Turkic Khaganates and the early medieval China. The authors consider the VI-VII centuries AD as an object of chronological research. In the 6th century, the first Turkic Khaganate was established and quickly became an important geopolitical neighbor of the Chinese Empire. The historical development of the Turkic Khaganate was closely linked to the Chinese Empire: it was the closest ally during periods of prosperity and the most significant threat during the Khaganate’s decline. In the 7th century, the Turks lost their statehood for half a century and were subjugated by the Tang Empire. Despite this, it was at this time that the influence of Turkic culture on Chinese culture increased. The mutual influence of cultures was manifested in the following areas: religion, various traditions, art, music, objects of material culture, architecture, etc. The research makes it possible to better understand the aspects of diplomatic relations between the states, the motives for the development of the foreign policy vector between them. The article analyzes historical sources and uses archaeological and anthropological materials, and uses methods of systematic complex analysis.